2021
DOI: 10.3897/zookeys.1055.68640
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological evidence reveals a new genus of the subfamily Heteropterinae (Lepidoptera, Hesperiidae) from China

Abstract: Molecular phylogenetic analysis indicates that the genus Carterocephalus is not monophyletic. Based on combined molecular and morphological evidence, we propose a new genus, Pulchroptera Hou, Fan & Chiba, gen. nov., for Pamphila pulchra Leech, 1891. The adult, wing venation, and male genitalia of Pulchroptera pulchracomb. nov., Carterocephalus palaemon, and related genera are illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“… Note : Characteristic descriptions of P. capitata , P. sichuanensis , P. yangshuoensis , and P. wuana are referenced from published works (Liu et al., 2023; Wu et al., 2022, 2023). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Note : Characteristic descriptions of P. capitata , P. sichuanensis , P. yangshuoensis , and P. wuana are referenced from published works (Liu et al., 2023; Wu et al., 2022, 2023). …”
Section: Resultsmentioning
confidence: 99%
“…Liu et al. (2023) suggested that P. wuana was closely related to P. yangshuoensis ( p ‐distance = 5.1%), and the phylogeny within the genus showed that the relationship was ( P. capitata + ( P. sichuanensis + ( P. yangshuoensis + P. wuana ))). Our phylogenetic framework was compatible with this and gave a better resolution of the affinities among these included taxa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We amplified a single mitochondrial gene (a 658-bp fragment of COI) using the general primers 1490-2198 ( Folmer et al 1994 ). The amplification protocol follows Hou et al (2021) . Sequences were aligned using Clustal W ( Thompson 1997 ) and edited manually using MEGA 7.0 ( Kumar et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%